Brain tissue and myelin volumetric analysis in multiple sclerosis at 3T MRI with various in-plane resolutions using synthetic MRI. - Saccenti, Laetitia; Andica, Christina; Hagiwara, Akifumi; Yokoyama, Kazumasa; Takemura, Mariko Yoshida; Fujita, Shohei; Maekawa, Tomoko; Kamagata, Koji; Le Berre, Alice; Hori, Masaaki; Hattori, Nobutaka; Aoki, Shigeki (Neuroradiology, 2019)
Purpose: Synthetic MRI (SyMRI) enables automatic brain tissue and myelin volumetry based on the quantification of R1 and R2 relaxation rates and proton density. This study aimed to determine the validity of SyMRI brain tissue and myelin volumetry using various in-plane resolutions at 3T in patients with multiple sclerosis (MS). Methods: We scanned 19 MS patients and 10 healthy age- and gender-matched controls using a 3T MR scanner with in-plane resolutions of 0.8, 1.8, and 3.6 mm. The acquisition times were 5 min 8 s, 2 min 52 s, and 2 min 1 s, respectively. White matter (WM), gray matter (GM), cerebrospinal fluid (CSF), and myelin and non-WM/GM/CSF (NoN) volumes; brain parenchymal volume (BPV); and intracranial volume (ICV) were compared between different in-plane resolutions. These parameters were also compared between both groups, after ICV normalization. Results: No significant differences in measured volumes were noted between the 0.8 and 1.8 mm in-plane resolutions, except in NoN and CSF for healthy controls and NoN for MS patients. Meanwhile, significant volumetric differences were noted in most brain tissues when compared between the 3.6 and 0.8 or 1.8 mm resolution for both healthy controls and MS patients. The normalized WM volume, myelin volume, and BPV showed significant differences between controls and MS patients at in-plane resolutions of 0.8 and 1.8 mm. Conclusions: SyMRI brain tissue and myelin volumetry with in-plane resolution as low as 1.8 mm can be useful in the evaluation of MS with a short acquisition time of < 3 min.